Additions of new species to Thelepus (Thelepodidae), with description of a new Terebellides (Trichobranchidae) from Taiwan - Hsueh, Pan-Wen; Li, Kuo-Rong (Zootaxa, 2017)
Following a recent report on two new species of Thelepus for the Taiwan, we describe two more new species, T. hemeiensis sp. nov. and T. wuchiensis sp. nov., for the genus. In addition, a new species of the Family Trichobranchidae is also described, Terebellides baliensis sp. nov., which was collected from an offshore monitoring survey in northwestern Taiwan. The genus Terebellides as well as the Family Trichobranchidae are reported for the first time from Taiwanese waters.